Polymorphism of MnSOD (Val16Ala) gene in pregnancies with blighted ovum: A case-control study - Asiyeh Moshtaghi; Hamidreza Vaziri; Reyhaneh Sariri; Hoorieh Shaigan (Shahid Sadoughi University of Medical Sciences, 2017)
Background: Blighted ovum is one of the most common reasons for abortion during the first three months of pregnancy. Manganese superoxide dismutase (MnSOD) is an important antioxidant enzyme in the human immune system. The gene is located on 6q25 chromosome and acts on mitochondrial matrix. In the case of mutation or inactivity of this enzyme, mitochondrial and nuclear DNA will severely be destructed. The most common polymorphism of its gene is Val16Ala. Objective: The aim was to investigate a possible mutation in pregnant women who had abortion during the first trimester of pregnancy due to blighted ovum. Materials and Methods: In this case-control study, 34 women were entered as the case and control groups, respectively. Genome DNA was extracted from saliva samples and its genotype was determined using Tetra-primer amplification refractory mutation system polymerase chain reaction technique. Results: In the case group, 16 (48%) cases had Val/Val genotype, 17 (50%) were heterozygote and had Val/Ala genotype, and 1 (2%) had Ala/Ala genotype. Among controls, 7 (22%) items had Val/Val genotype, 6 (17%) had Val/Ala genotype, and 21 (61%) had Ala/Ala genotype. The frequency of TT, CT, and CC genotypes was 48%, 50%, and 2% in case group and 22%, 17%, and 61% in control group, respectively. Statistical analysis revealed a significant relationship between Val16Ala polymorphism of MnSOD gene and blighted ovum (p= 0.0003). Conclusion: It has concluded that a significant relationship exists between Val16Ala polymorphism of MnSOD gene and blighted ovum.